2021
DOI: 10.1017/s1352465821000436
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal dysfunction in individuals high in chronic worry: relations with interpersonal problem-solving

Abstract: Background: Interpersonal dysfunction has been proposed as an important maintenance factor in chronic worry and generalized anxiety disorder (GAD). Perceptions of problems and the problem-solving process as threatening, and unhelpful (e.g. avoidant, impulsive) problem-solving styles are implicated in worry and have also been suggested to be associated with dysfunctional interpersonal styles. Aims: The present study assessed the relationships between interpersonal dysfunction and problem-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…When interns have disagreements with their potential coworkers or superiors, their job satisfaction suffers and this can lead to feelings of anxiety and uncertainty about one's future. This finding is compatible with a study undertaken by Malivoire and Koerner (2022) reported that interpersonal conflict with co-workers has a positive relationship with anxiety. A positive relationship means that as the level of interpersonal conflict with co-workers increases, so does the level of anxiety experienced by the individuals involved in those conflicts.…”
Section: Reliability and Correlationsupporting
confidence: 93%
“…When interns have disagreements with their potential coworkers or superiors, their job satisfaction suffers and this can lead to feelings of anxiety and uncertainty about one's future. This finding is compatible with a study undertaken by Malivoire and Koerner (2022) reported that interpersonal conflict with co-workers has a positive relationship with anxiety. A positive relationship means that as the level of interpersonal conflict with co-workers increases, so does the level of anxiety experienced by the individuals involved in those conflicts.…”
Section: Reliability and Correlationsupporting
confidence: 93%
“…Effectively managing anxiety is of paramount importance for middle-aged adults, as untreated anxiety can have a profound and detrimental impact on their overall quality of life and well-being (Wilmer et al, 2021). As highlighted in studies, anxiety left unaddressed can lead to decreased productivity and strained social relationships (de Oliveira et al, 2023;Malivoire & Koerner, 2022), eroding life satisfaction and daily functioning (Saldivia et al, 2023). Furthermore, untreated anxiety can result in enduring consequences, potentially shaping the course of one's life and contributing to long-term emotional, psychological, and physical health challenges (Altamura et al, 2013;Kang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%